Design and hydraulic performance studies on an axial lead‐bismuth pump for GEN‐IV reactors. (6th August 2020) - Wang, Kailin; Li, Liangxing; Wang, Yanbo; Zhang, Shuanglei
Summary: Lead or lead‐alloy‐cooled fast reactors (LFRs) have been proved to be the most promising generation IV reactors with high performance in neutron economy, thermal hydraulics and security features. When lead‐bismuth eutectic (LBE) is used as coolant for LFR, the primary LBE pump is a key conveying equipment in LFRs, because it pumps liquid LBE to remove decay heat produced by core. The hydraulic performance and coolant flow velocity of LBE coolant pump is of great importance for the safety aspects concerning LFRs. This study aims to design an axial LBE pump firstly based on the theory of planar cascade and streamline method, then establishes three‐dimensional model of the axial LBE pump and performs the simulation analysis based on Ansys CFX software to study the impact of design parameters on LBE pump hydraulic performance. The results show that the highest flow velocity occurs at the blade of pump and it increases with the rotating speed, while the pump efficiency and pump head appear up‐down tendency as the flow rate increasing. The optimum rotating speed and the corresponding impeller parameters are proposed based on the theoretic and numerical studies. The research work will provide a theoretical basis and referred solution for the design of primary pump small module LFRs.